Open Research Problems in Network Security IFIP WG 11.4 International Workshop, iNetSec 2010, Sofia, Bulgaria, March 5-6, 2010, Revised Selected Papers - Camenisch, Jan; Kisimov, Valentin; Dubovitskaya, Maria (Security and Cryptology, 2011)
This book constitutes the refereed post-conference proceedings of the IFIP WG 11.4 International Workshop, iNetSec 2010, held in Sofia, Bulgaria, in March 2010. The 14 revised full papers presented together with an invited talk were carefully reviewed and selected during two rounds of refereeing. The papers are organized in topical sections on scheduling, adversaries, protecting resources, secure processes, and security for clouds.